"We want financial accountability": deconstructing tensions of community participation in CHPS, Ghana. Issue 6 (17th August 2016) - Yeboah, Thomas; Jagri, Francis
ABSTRACT: This article reports on the ways and factors that facilitate or constrain community participation in the Community-based Health Planning and Services (CHPS) programme in Nsanfo, a village in Central Region of Ghana. We found that the community made an important step through mobilising the necessary resources in establishing the CHPS compound, which has resulted in improved access to health care. Yet maintaining the facility did not matter most to community members, owing chiefly to unmet demands for financial accountability pertaining to the running of the programme. Failure to clearly identify various actors and their roles potentially explains this state of affairs.